2021
DOI: 10.3390/biom11091379
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biology Networks and Key Gene Regulators for Inflammatory Biomarkers Shared by Breast Cancer Development: Multi-Omics Systems Analysis

Abstract: As key inflammatory biomarkers C-reactive protein (CRP) and interleukin-6 (IL6) play an important role in the pathogenesis of non-inflammatory diseases, including specific cancers, such as breast cancer (BC). Previous genome-wide association studies (GWASs) have neither explained the large proportion of genetic heritability nor provided comprehensive understanding of the underlying regulatory mechanisms. We adopted an integrative genomic network approach by incorporating our previous GWAS data for CRP and IL6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
(81 reference statements)
1
1
0
Order By: Relevance
“…The IL-6-and TNFR2-associated pathways are emerging as critical mediators of inflammation-associated cancers, including ovarian malignancy [30,64,70,71,[76][77][78][79][80]. In our study, we found a significant overlapping contribution of TNFR2-expressing Tregs and IL-6 in predicting ovarian malignancy.…”
Section: Discussionsupporting
confidence: 57%
“…The IL-6-and TNFR2-associated pathways are emerging as critical mediators of inflammation-associated cancers, including ovarian malignancy [30,64,70,71,[76][77][78][79][80]. In our study, we found a significant overlapping contribution of TNFR2-expressing Tregs and IL-6 in predicting ovarian malignancy.…”
Section: Discussionsupporting
confidence: 57%
“…We aggregated the modules for each pathway in NP and IP separately. We then merged the modules from NP and IP for an overlapping pathway where more than 15% of genes are overlapped in both NP and IP and created 47 functionally categorized supernets [ 33 ].…”
Section: Methodsmentioning
confidence: 99%